Multiple Mediating Effects of Conflicts With Parents and Self-Esteem on the Relationship Between Economic Status and Depression Among Middle School Students Since COVID-19 - Lee, Jaewon; Lim, Hyejung; Allen, Jennifer; Choi, Gyuhyun (Frontiers in Psychology, 2021)
This study explores the underlying associations between perceived economic status and depression among middle school students during COVID-19 in the context of conflict with parents and self-esteem. 328 middle school students were included, and a multiple mediator model was employed to examine the dual mediating effects. Middle schoolers’ household economic status was negatively associated with their conflict with parents. Conflict with parents was negatively related to middle school students’ self-esteem. Indirect effects of perceived economic status via conflict with parents was significantly associated with depression. The indirect effect of perceived economic status via both conflict with parents and self-esteem was related to depression. Government subsidies should temporarily be expanded to improve households’ economic status to potentially improve middle school students’ depression and to enhance relationships between children and their parents during the COVID-19 pandemic. Further, extra financial support from the government should be focused on poor households with children in order to address family conflict, self-esteem, and depression among middle school students.